A study of noise induced health problems in Lucknow city, Uttar Pradesh, India - Dipak Prasad , (National Geographical Journal of India, 2023)
The World Health Organization (WHO) has identified noise pollution as the third most hazardous form of pollution, posing significant health risks in urban areas, following air and water pollution. Prolonged noise exposure causes adverse health effects, including hypertension, anxiety, depression, hormonal imbalances, and elevated blood pressure, which can ultimately lead to heart problems. Lucknow city, in the Middle Gangetic Plain, faces exacerbated noise pollution due to transport, industrial activities, and machinery. The rapid industrialization and urbanization, coupled with an unplanned transport system, congested roads, the prevalence of older vehicles, and high population density, have escalated the already dire situation to its peak in the city. The study aims to assess the impact of noise on the health of the population. The primary data was collected from 35 stations within study area. Both thematic mapping and perception studies have been conducted to gain insights into the distribution pattern of noise pollution and its impact on health. The noise levels in the city exceed the standard limits across various zones, including residential areas (55 dBA), commercial zones (65 dBA), industrial zones (75 dBA), and even silence zones (50 dBA). A statistical analysis of health issues, such as hearing loss, mental disorders, heart problems, cholesterol levels, headaches, and nausea, has revealed a significant direct correlation between the prevalence of these problems and the noise levels within the study area.